2021
DOI: 10.1038/s41598-021-86608-1
|View full text |Cite
|
Sign up to set email alerts
|

Persimmon-derived tannin ameliorates the pathogenesis of ulcerative colitis in a murine model through inhibition of the inflammatory response and alteration of microbiota

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) induced by dysregulation of the immune response in the intestinal mucosa. Although the underlying mechanisms of UC development are not fully understood, disruption of gut microbiota, “dysbiosis”, is thought to lead to the development of IBD. Persimmon (Ebenaceae Diospyros kaki Thunb.)-derived tannin, which is a condensed polymeric tannin consisting of catechin groups, has antioxidant, anti-inflammatory, and antimicrobial activities. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 48 publications
1
18
1
Order By: Relevance
“…The procedure for persimmon-derived tannin extraction has been described previously 8 , 9 . Immature persimmon fruits (Ebenaceae Diospyros kaki Thunb., cv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for persimmon-derived tannin extraction has been described previously 8 , 9 . Immature persimmon fruits (Ebenaceae Diospyros kaki Thunb., cv.…”
Section: Methodsmentioning
confidence: 99%
“…The four types of catechin—epicatechin (EC), epicatechin gallate, epigallocatechin, and epigallocatechin gallate (EGCG)—are condensed into chains of 19–47 molecules long 7 . Because of its large molecular size, the persimmon tannin has strong antioxidant, immunomodulatory, and antimicrobial activities 6 , 8 . We have previously shown that dietary intake of the soluble fraction of persimmon-derived tannin attenuated Mycobacterium avium complex (MAC) infection in an in vivo mouse model 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that female mice were administered DSS in drinking water to induce colitis through alteration of the microbiota composition and immune response, this ability of DSS to alter gut microbiota composition can be targeted for IBD therapy (Kitabatake et al, 2021;Yang et al, 2021). We observed that the use of 5% (w/v) DSS in drinking water for 7 days induced inflammation in the entire colon and led to an increase in the incidences of metaplasia and tumour formation in both rats and mice (Murthy et al, 1993).…”
Section: Discussionmentioning
confidence: 73%
“…The procedure for persimmon-derived tannin extraction has been described previously [ 23 , 24 , 25 ]. Immature persimmon fruits ( Diospyros kaki Thunb., cv.…”
Section: Methodsmentioning
confidence: 99%